ANALYSIS OF MATHEMATICS LEARNING MOTIVATION FOR JUNIOR HIGH SCHOOL GRADE 7 IN THE IMPLEMENTATION OF THE KURIKULUM MERDEKA - Yazidah, Nok Izatul; Khairunisa, Helda; Sulistyorini, Yunis (FKIP Universitas Muhammadiyah Tangerang, 2025)
Learning motivation is one of the crucial factors that influence students' success in understanding subject matter, including mathematics which is often considered challenging. This study aims to examine the level of student motivation in learning mathematics in the implementation of the Independent Curriculum, identify various factors that influence learning motivation, and evaluate the effectiveness of the Independent Curriculum itself. Using a qualitative descriptive approach through interview and observation methods, this study found that most students showed learning motivation at a moderate level, while only a few were at a high or low level of motivation. Various factors that influence learning motivation consist of internal and external factors. The implementation of the Independent Curriculum is considered to provide flexibility for students with high motivation, but has not fully supported students with low motivation due to limited teacher training and learning resources. The conclusion of this study is that the Independent Curriculum has a great opportunity to increase student learning motivation if supported by the implementation of personal learning strategies, increasing teacher competence, and utilizing innovative learning technology.